2016
DOI: 10.1152/ajpendo.00211.2015
|View full text |Cite
|
Sign up to set email alerts
|

Profound hyperglycemia in knockout mutant mice identifies novel function for POU4F2/Brn-3b in regulating metabolic processes

Abstract: -The POU4F2/Brn-3b transcription factor has been identified as a potentially novel regulator of key metabolic processes. Loss of this protein in Brn-3b knockout (KO) mice causes profound hyperglycemia and insulin resistance (IR), normally associated with type 2 diabetes (T2D), whereas Brn-3b is reduced in tissues taken from obese mice fed on high-fat diets (HFD), which also develop hyperglycemia and IR. Furthermore, studies in C 2C12 myocytes show that Brn-3b mRNA and proteins are induced by glucose but inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…As a TF, Brn-3b(s) regulates multiple target genes and thereby drive complex cellular effects. Here we show that known Brn-3b target genes, cyclin D1 34 , GLUT4 30 and Bax 40,41 , are increased by AngII in intact hearts, isolated NRVM cultures or H9c2 cells. Time-course studies identify differential expression patterns of Brn-3b target genes following AngII treatment with maximal expression of cyclin D1 and GLUT4 seen at earlier time points when pro-apoptotic Bax expression is low but are reduced by 24 h, when Bax is maximally induced.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…As a TF, Brn-3b(s) regulates multiple target genes and thereby drive complex cellular effects. Here we show that known Brn-3b target genes, cyclin D1 34 , GLUT4 30 and Bax 40,41 , are increased by AngII in intact hearts, isolated NRVM cultures or H9c2 cells. Time-course studies identify differential expression patterns of Brn-3b target genes following AngII treatment with maximal expression of cyclin D1 and GLUT4 seen at earlier time points when pro-apoptotic Bax expression is low but are reduced by 24 h, when Bax is maximally induced.…”
Section: Discussionmentioning
confidence: 71%
“…For example, cyclin D1 KO mice display attenuated hypertrophy, whereas transgenic mice over-expressing cyclin D1 develop enlarged hearts 16,17 . Similarly, GLUT4, is increased in hypertrophic hearts 30 and may contribute to metabolic switching, from fatty acid to glucose metabolism in stressed hearts 54 . In contrast, induction of Bax and p53 are linked to cardiomyocyte apoptosis in failing hearts 25,62,63 .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies indicate the molecular mechanisms developing insulin resistance are based on various specific molecules such as cytokines [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. This information [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , ...…”
Section: Introductionmentioning
confidence: 99%
“…Brn-3b is a tissue-specific TF [18][19][20][21][22][23][24][25] belonging to the class IV POU (Pit-1; Oct-1; Unc-86) sub-family of homeodomain TFs, and is characterised by a highly conserved POU domain that forms a helix-turn-helix (HTH) DNA binding structure 26 . The POU domain consists of a 60aa homeodomain, POU-HD , with strong similarity to homeobox proteins and 74-82aa POU-specific domain (POU s ), which is unique to POU proteins (Fig.…”
Section: Brn-3b/pou4f2 Transcription Factor (Tf)mentioning
confidence: 99%
“…afferents of dorsal root ganglia (DRG); cranial nerves V, VIII, IX, X and VII 37 . However, subsequent studies have shown Brn-3b expression in other diverse tissues including reproductive tract tissue (testis, ovary and breast epithelium) 22,33,34,[38][39][40][41][42][43][44] , peripheral blood mononuclear cells (PBMC) 23,45,46 , metabolic tissue (adipocytes, skeletal muscle and liver) 20 , cardiovascular tissues e.g. cardiomyocytes 18,19,21,39,47 and vascular smooth muscle cells (VSMC) (Fig.…”
Section: Brn-3b/pou4f2 Transcription Factor (Tf)mentioning
confidence: 99%